Effect of different dates of transplanting and harvesting on the morphology and andrographolide content in Andrographis paniculata - Phurailatpam, A.K.; Maiti, S.; Maiti, G. G. (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Â  An experiment was conducted at Directorate of Medicinal and Aromatic Plants Research, Anand on the effect of different dates of transplanting and different dates of harvesting on the change in the morphology and chemical content in three accessions of Andrographis paniculata. Same aged seedlings were transplanted at four different dates at 15 days interval. The plants were harvested at three different dates at 90, 105 and 120 days after transplanting (DAT). Morphological data and chemical data were collected at different intervals. It was observed that different dates of ransplanting significantly influenced the plant height, number of leaves per plant, fresh and dry herbage, stem and leaf yields and andrographolide yield. Andorgrapholide content in leaf decreased with delayed transplanting; but in stems, andrographolide content increased with delayed transplanting. Andrographolide yield in leaves and herbage increased with early transplanting whereas in stems, delayed transplanting resulted in more andrographolide yield. All the morphological characters were recorded maximum as well as the andrographolide content in herbage were maximum at 120 DAT harvesting. However, andrographolide yield in leaf and herbage were maximum at 105 DAT harvesting. There was not much significant influence of the interaction ofÂ  transplanting dates and harvesting dates except few morphological characters viz. plant height, number of primary branches, stem diameter and number of leaves per plant. There was no significant influence of the interaction of accessions and harvesting time on any characters. The yield of andrographolide was calculated as maximum in accession 1 and accession 3 at age 120 DAT when the stem : leaf ratio became 1:2 having the indication that this ratio can be fixed as harvesting index in A. paniculata and accordingly harvesting of the crop can be advised to achieve maximum yield of crude drug. So, an early transplanting (15-30 July) and a late harvesting (105-120 DAT) would be an ideal for the cultivation of this crop so to get maximum yield in herbage as well as andrographolide content.